Tracheal cuff pressure change before and after the performance of nursing care - Lúcia Marinilza Beccaria; Thays Marley Antonio Doimo; Nádia Aparecida Antonia Polletti; Tais Pagliuco Barbosa; Daniele Cristiny da Silva; Alexandre Lins Werneck
ABSTRACT Objective: Verify the changes of endotracheal cuff pressure before and after oral hygiene, head-of-bed elevation at 0º, 30º, and 60º, change in body position, aspiration of the endotracheal tube, and in-bed bathing. Method: The study sample was composed of 88 patients. We performed 3,696 checks from July to September 2014. Results: Pressure values were analyzed in seven nursing care in the morning. Six of them were significantly altered before and after nursing procedure. In the afternoon, five of the health care provided were altered, and in the evening, only two. Most of pressure values were below recommended. Conclusion: There were differences before and after health care provided, showing changes in cuff pressure. In-bed bathing and head-of-bed elevation at 30º were the ones that most altered pressure values in the three working shifts. Therefore, it is necessary to measure cuff pressure at least twice per working shift, preferably after bathing.